Factors Influencing Job Hopping Intention Among Gen-Y Employees In The ICT Industry In Malaysia - Munusamy, Murali (2012)
This study is meant to identify factors influencing job hopping intention among generation Y employees in the information and communication technology (ICT) industry in Malaysia. The findings of this study show that job hopping is common among Gen-Y employee working in the ICT industry in Malaysia.